TUJUAN HIDUP MANUSIA Thomas Aquinas dan Dewa Ruci - Gregorius Kukuh Nugroho (Litbang STFT Widya Sasana Malang, 2015)
The study is a comparative study of Thomas Aquinas and Dewa Ruci on purpose of human life as comparaton between Western and Eastern philosophy. Aquinas is the representative of the Western philosophy, whereas Dewa Ruci is sort of philosophical legacy of the Est. Dealing with idea of Aquinas on purpose of human life I go to the Summa Theologica. Aquinas gives an interesting ideas worthed to explore. Dewa Ruci is that of “Serat”, a Javanese literature on the lived experience of the so-called Bima who transformed himself into Dewa Ruci after undergoing spiritual retreat. The “Serat” contains philosophical wisdom typically Javanese and “Eastern” particularly related to “divine” purpose of human life.